DIRECTIONS FOR IMPROVING THE EFFICIENCY OF E-COMMERCE ENTITIES - DZYUBINA, Andriy; ZELENIUKH, Ostap (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article addresses the critical need to enhance the operational and strategic efficiency of e-commerce entities in a rapidly evolving digital economy. It aims to systematize mechanisms and strategies to optimize business processes, reduce costs, and improve customer experiences. It is highlighted several challenges such as high operational costs, logistics inefficiencies, limited adoption of advanced technologies, and adaptability issues in e-commerce. These are linked to broader scientific and practical tasks, including digital transformation, sustainable business models, and global economic integration, emphasizing the role of technologies like AI, big data analytics, and automation. It is proposed a structured approach to align tools with specific operational and strategic goals. The study outlines 14 interconnected factors for improving efficiency, including personalization, logistics optimization, AI, omnichannel strategies, cybersecurity, AR/VR, social commerce, and sustainability. These are synthesized in a comprehensive table, illustrating their impact with examples. The framework emphasizes consumer trust, cost reduction, and market adaptability. It is provided a robust framework for e-commerce entities to achieve operational excellence through technology integration, consumer-centric strategies, and sustainability. Future research should focus on scalable solutions for SMEs, cross-border regulatory strategies, generative AI, blockchain, real-time analytics, and workforce upskilling to sustain long-term efficiency gains. This work offers practical and scientific value by addressing unresolved challenges and providing a cohesive methodology for e-commerce entities to thrive in a competitive, digital landscape.